A Commentary to Hegel’s Science of Logic - Carlson, David Gray. author. aut Link
XIII, 632 p. 1 illus.
Keywords: Hegel is regarded as the pinnacle of German idealism and his work has undergone an enormous revival since 1975. In this book, David Gray Carlson presents a systematic interpretation of Hegel's 'The Science of Logic', a work largely overlooked, through a system of accessible diagrams, identifying and explicating each of Hegel's logical derivations.